Volume 1: Fora, Parts A, B, C, and D 2003
DOI: 10.1115/fedsm2003-45641
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Effects on Wall Shear in Vortical Flows

Abstract: Direct numerical simulations of the motion of bubbles in turbulent flows are being carried out, using a finite volume/front tracking technique that accounts fully for the effect of fluid inertia, viscosity, bubble deformability, and surface tension. The objective of the simulations is both to address the fundamental interaction mechanisms between the bubbles and the flow and how the bubbles modify the wall turbulent structures, as well as to provide data for validation of simplified models. Results for bubbles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Recently, Echavarren and co-workers synthesized closely related dimeric oxapalladacycle phosphine complex 15 starting from o-iodobenzyl alcohol, and its structure was clearly established by X-ray crystallography. 27 Moreover, 15 proved to react with t BuNC at 23 °C to give rise to imidate 16 in 54% yield (vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Echavarren and co-workers synthesized closely related dimeric oxapalladacycle phosphine complex 15 starting from o-iodobenzyl alcohol, and its structure was clearly established by X-ray crystallography. 27 Moreover, 15 proved to react with t BuNC at 23 °C to give rise to imidate 16 in 54% yield (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar way, the combination of 1-hexynylboronate 2a and 2,8-heptadiyne- Finally, we briefly examined the four-component coupling including an isocyanide in place of CO (Scheme 9). Recently, the reactions of aza-or oxapalladacycles with isocyanides were independently investigated by Vicente and Echavarren, 27,33 and the palladium-catalyzed syntheses of amidines and imidates from aryl halides were developed by Whitby and co-workers. 34 The ruthenium-catalyzed cyclotrimerization of 2a, 3a, and 4a and the palladium-mediated reaction of the resultant cyclic arylboronate 6aaa with t BuNC at room temperature for 24 h gave cyclic imidate 23 in 36% yield after purification with alumina column chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…Full details of VTST calculations are given elsewhere. 383,401,402 Next we present some examples to illustrate the difference between conventional TST, CVT, and µVT. Ferna ´ndez-Ramos et al 403 used ab initio dual-level direct dynamics to study the Cl + C 2 H 6 f ClH + C 2 H 5 hydrogen abstraction reaction.…”
Section: Cvtmentioning
confidence: 99%
“…Specifically, this effective mass is a function of the reaction path curvature. 360,511,514 The final version of this approach 401,402,515 is called the small-curvature tunneling (SCT) approximation, and the effective mass is given by where t h(s) is a suitably averaged value of the mass-scaled normal coordinate u m at the zero-point-energy turning point of mode m on the concave side of the MEP, and a j(s) is a suitably averaged value of where κ m (s) is the component of the reaction-path curvature vector κ(s) in the direction of mode m. Note that the corner cutting due to the negative centrifugal effect raises the tunneling probability, contrary to earlier 516 assumptions. This is because the path is shortened but not enough to raise the effective potential for tunneling.…”
Section: Tunneling Recrossing and The Transmission Coefficientmentioning
confidence: 99%
“…Direct numerical simulation (DNS) of turbulent bubbly flows has been conducted in the search for mechanisms. Unfortunately, such studies are only possible at modest Reynolds numbers but have been attempted in free shear flows (Druzhinin & Elghobashi 1998), and channel flows (Xu, Maxey & Karniadakis 2002;Fernández, Lu & Tryggvason 2003;Vance et al 2003), and in a turbulent boundary layer (Ferrante & Elghobashi 2004). In these studies, bubbles were found to migrate into and disrupt vortical structures.…”
Section: Introductionmentioning
confidence: 99%